Specific Issues of Mandatory Nature and Discretionary Nature of Shareholders Legal Relations’ Regulation - E. M. Bondariev (Law and Safety)
Specific issues of the correlation of mandatory nature and discretionary nature of shareholders legal relations’ regulation have been researched. Based on the analysis of the legislation of Ukraine and other countries, the author has paid attention to the fact that priority should be given to their imperative provision in the framework of shareholders legal relations.